3-D micromorphological comparison of human and carnivore tooth marks - Gniewek, Erin M., author; Pante, Michael C., advisor; Glantz, Michelle M., committee member; Boone, Randall B., committee member (Colorado State University. Libraries, 2025)
The archaeological record may reveal a deep history of ancient human cannibalism, but modern researchers face substantial challenges when it comes to confirming such a history. While archaeologists often examine ancient human remains for signs of human consumption (cut marks, burned bone, etc.), such evidence is only suggestive of ancient human cannibalism, not definitive – as these markings could result from non-consumptive practices, such as artistic modifications, funerary rituals, and natural fires. The most direct evidence of ancient human cannibalism is the presence of human tooth marks on ancient human bone, as these marks can be directly linked to the act of consumption. However, due to similarities between human and carnivore tooth marks, distinguishing between the two when using traditional analytical methods is challenging. Therefore, the goals of this research were twofold: one, to develop a quantitative database that accurately characterizes the morphology of human tooth marks, and two, to statistically compare human tooth mark data with that of carnivores to develop more reliable human tooth mark identification criteria. An experiment was conducted in which ten human participants consumed the meat of two cooked pig bones using only their teeth, producing a total of 126 human tooth marks. These marks were then 3-D scanned using a Sensofar S Neox 3-D optical profilometer and subsequently measured using Digital Surf's MountainsMap® software. Lastly, the human tooth marks were statistically compared to 898 experimentally produced bone surface modifications of known origin, including 275 carnivore tooth marks. Results indicate that human tooth marks are distinguishable from those produced by carnivores – 91.3% of the 126 human tooth marks were correctly classified as human-made when compared to the sample of 275 carnivore tooth marks. Additionally, human tooth marks were classified correctly 86.5% of the time when compared to 898 experimentally produced bone surface modifications including stone tool cut marks, trample marks, hammerstone percussion marks, and carnivore tooth marks. Overall, this 3-D analysis and statistical comparison demonstrates that human tooth marks are quantitatively distinct from carnivore tooth marks and other bone surface modifications. Applying these findings to the archaeological record will significantly advance researchers' understanding of ancient human diets related to the consumption of meat and bone, including those that may even be cannibalistic.
Keywords: ancient human cannibalism; human tooth marks; taphonomy; bone surface modifications; 3D optical profilometer; quantitative methods